Where's the beef? Retail channel choice and beef preferences in Argentina - Colella, Florencia Manon; Ortega, David Leonardo (2018)
Argentinean beef is recognized and demanded internationally. Locally, consumers are often unable to afford certified beef products, and may rely on external cues to determine beef quality. Uncovering demand for beef attributes and marketing them accordingly, may require an understanding of consumers' product purchasing strategies, which involves retailer choice. We develop a framework utilizing latent class analysis to identify consumer groups with different retailer preferences, and separately estimate their demand for beef product attributes. This framework accounts for the interrelationship between consumers' choice of retail outlets and beef product preferences. Our analysis of data from the city of Buenos Aires identifies two groups of consumers, a convenience- (67percent) and a service- (33percent) oriented group. We find significant differences in demand for beef attributes across these groups, and find that the service oriented group, while not willing to pay for credence attributes, relies on a service-providing retailer-namely a butcher-as a source of product quality assurance.